Prevalence of Low Back Pain and Associated Risk Factors among Nursing and Midwifery Students in Indonesia: A Cross-Sectional Study - Harto, Toto; Ferdi, Roni; Akbar, M. Agung (Journal of Health and Nutrition Research, 2025)
Low Back Pain (LBP) commonly affects health science students due to academic and clinical demands, yet remains underreported and insufficiently addressed in educational settings. This study aims to analyze the risk factors associated with low back pain complaints among nursing and midwifery students. A cross-sectional study was conducted involving 126 students from the School of Health Science Al-Ma’arif Baturaja. Total sampling was used. Data were collected using validated questionnaires assessing sitting duration, sitting posture, body mass index (BMI), gender, and physical activity. Data analysis included univariate and bivariate tests. The prevalence of LBP complaints among students was 66.7%. Bivariate analysis showed that BMI (p = 0.029), sitting duration (p = 0.008), and sitting posture (p = 0.003) were significantly associated with LBP. In contrast, gender (p = 0.183) and physical activity (p = 0.117) were not significantly related. Modifiable risk factors such as abnormal BMI, prolonged sitting, and non-ergonomic posture contribute significantly to LBP among students. Gender and activity level were not major predictors in this study. Educational institutions should integrate ergonomic education and preventive health programs into nursing and midwifery curricula to mitigate LBP risks. Early intervention strategies focusing on behavior and posture may enhance student well-being and academic performance.